Let's dive together - Fyrigou Consolo, G. (LEN European Aquatics, 2012)
This book, written by the chairman of the technical diving committee of the European diving organisation LEN is about the organisation and operation of diving events, diving equipment, description and specifications, judging diving events, diving development, history of diving and statistics. It provides also an index of European diving venues and facilities.